Human–animal chimeras: ethical issues about farming chimeric animals bearing human organs. Issue 1 (December 2016) - Bourret, Rodolphe; Martinez, Eric; Vialla, François; Giquel, Chloé; Thonnat-Marin, Aurélie; De Vos, John
Abstract Recent advances in stem cells and gene engineering have paved the way for the generation of interspecies chimeras, such as animals bearing an organ from another species. The production of a rat pancreas by a mouse has demonstrated the feasibility of this approach. The next step will be the generation of larger chimeric animals, such as pigs bearing human organs. Because of the dramatic organ shortage for transplantation, the medical needs for such a transgressive practice are indisputable. However, there are serious technical barriers and complex ethical issues that must be discussed and solved before producing human organs in animals. The main ethical issues are the risks of consciousness and of human features in the chimeric animal due to a too high contribution of human cells to the brain, in the first case, or for instance to limbs, in the second. Another critical point concerns the production of human gametes by such chimeric animals. These worst-case scenarios are obviously unacceptable and must be strictly monitored by careful risk assessment, and, if necessary, technically prevented. The public must be associated with this ethical debate. Scientists and physicians have a critical role in explaining the medical needs, the advantages and limits of this potential medical procedure, and the ethical boundaries that must not be trespassed. If these prerequisites are met, acceptance of such a new, borderline medical procedure may prevail, as happened before for in-vitro fertilization or preimplantation genetic diagnosis.